Bioanalytical profile of the L-arginine/nitric oxide pathway and its evaluation by capillary electrophoresis - Boudko, Dmitri Y. (2007)
This review briefly summarizes recent progress in fundamental understanding and analytical profiling of the L-arginine/nitric oxide (NO) pathway. It focuses on key analytical references of NO actions and on the experimental acquisition of these references in vivo, with capillary electrophoresis (CE) and high-performance capillary electrophoresis (HPCE) comprising one of the most flexible and technologically promising analytical platform for comprehensive high-resolution profiling of NO-related metabolites. Second aim of this review is to express demands and bridge efforts of experimental biologists, medical professionals and chemical analysis-oriented scientists who strive to understand evolution and physiological roles of NO and to develop analytical methods for use in biology and medicine.